A Flexible Array for Cardiac 31P MR Spectroscopy at 7 T - Roat, Sigrun; Vít, Martin; Wampl, Stefan; Schmid, Albrecht Ingo; Laistler, Elmar (Frontiers in Physics, 2020)
Purpose: The simulation optimization and implementation of a flexible 31P transmit/receive coil array, under the geometrical constraint of fitting into the housing of an already existing 12-channel proton array, to enable localized cardiac 31P MRS at 7 T is presented. Methods: The performance in terms of homogeneity, power and SAR efficiency of 32 potential array designs was compared by full wave 3D electromagnetic simulation considering the respective optimal static B1+ shims. The design with the best performance was built and compared to a commercially available single loop in simulation and measurement. Results: Simulation revealed an optimal array design comprising three overlapping elements, each sized 94 x 145 mm2. Simulation comparison with a single loop coil predicted a performance increase due to increased power efficiency and lower SAR values. This was verified by phantom measurements, where an SNR increase of 46% could be observed for localized 31P spectroscopy in a voxel positioned comparable to an in vivo cardiac measurement scenario. Conclusion: A flexible 31P/1H RF coil array with improved SNR is presented, enabling localized in vivo cardiac 31P spectroscopy at 7 T.